Buckling Analysis of Functionally Graded Carbon Nanotube-reinforced Composite Plates using Incremental Loading and Dynamic Relaxation Methods - M. E. Golmakani; V. Zeighami (Ravish/hā-yi ̒adadī dar Muhandisī, 2016)
In this paper, buckling behavior of functionally graded carbon nanotube-reinforced composite (FG-CNTRC) plates is studied in line with the plates thikness. All  governing equations are presented incrementally, based on a First-order Shear Deformation Theory (FSDT) of plates and von Karman strain field. In order to find the critical buckling load, the axial load is applied to the plate incrementally and the equilibrium equations are solved by Dynamic Relaxation (DR) method. Parametric study of the effects of volume fraction of Carbon Nanotubes (CNTs), CNTs distribution, plate width-to-thickness ratio and aspect ratio of nano composite plates is done in detail. The results show that functionally graded distribution of CNTs causes a significant increase of critical buckling load.